Development of a Three-Axis Monolithic Flexure-Based Ground Reaction Force Sensor for Various Gait Analysis - Jang, Seung Yeon; Youn, Jung Hwan; Lim, Su Hyun; Kim, Seong Su; Kim, Uikyum; Kyung, Ki Uk (IEEE Robotics and Automation Letters, 2022)
In this letter, we developed a monolithic flexure-based three-axis ground reaction force (GRF) sensor to analyze various gaits, including walking, running, and jumping. The GRF sensor requires different force capacities on each axis. In order to satisfy the force range requirements, a simple circular cross-section flexure was designed. The use of a monolithic flexure allows the sensor to have broad measurement range with enhanced durability in a compact, simple and lightweight structure. The proposed sensor can measure vertical force up to 2400 N and shear force up to 240 N that can measure wide range of GRF for walking, running and jumping. The deformation of the flexure under applied force is measured through capacitance changes and these values are converted into the three-axis force. The performance of the sensor was evaluated through several experiments. An outsole GRF measurement system was designed by embedding two developed sensors. The resultant GRF data during several in-place motions were measured with the developed system.
Keywords: Analysis and synthesis; Force; Force sensing; Forces measurements; Human and humanoid motion analyse and synthesis; Legged locomotion; Physical humanrobot interaction (phri); Robot sensing system; Tactile sensing; Task analysis; Force and tactile sensing; human and humanoid motion analysis and synthesis; physical human-robot interaction